Adopsi Teknologi Data Analytics dan Artificial Intelligence (AI) dalam Peningkatan Efisiensi Prosedur Analitis Audit - Muh. Az’har; Nurul Annisa; Masyhuri Masyhuri (Journal of Economic and Business Advancement, 2025)
The increasingly complex and digitized business environment has driven fundamental changes in auditing practices, particularly in analytical procedures that demand greater efficiency, accuracy, and scope of examination. This study aims to analyze the adoption of data analytics and artificial intelligence technologies in improving the efficiency of analytical audit procedures and their implications for audit quality and the role of professional auditors. The research method used is qualitative with a literature study and conceptual analysis approach through a systematic review of scientific literature, reputable journals, institutional reports, and relevant professional auditing standards. The results and discussion show that the use of analytical technology can broaden the scope of audits, accelerate risk assessment, improve the quality of audit evidence, and support the detection of anomalies and potential fraud more effectively than conventional procedures. The adoption of this technology also brings challenges related to human resource readiness, professional ethics, and audit governance. This study concludes that the integration of analytical technology into audit procedures is a strategic step that improves audit efficiency and quality, provided that it is supported by the development of auditor competencies and an adequate governance framework.